Spermatozoon of the wild scalloped perchlet, Ambassis nalua (Hamilton, 1822): Ultrastructure and morphometric analysis - Nutchar Sukkhee (2022)
The description of sperm morphology is fundamental in the reproductive biology of fishes, but this information is limited in the family Ambassidae. Our report hence focused on the ultrastructure and morphometric analysis of spermatozoa in a pelagic fish Ambassis nalua. All fish (n = 75) were obtained during January and March 2017 from the Estuarine Pranburi River, Thailand. The standard length of fish used in this study was 3.4 ± 0.12 cm (mean ± standard deviation). All specimens were considered mature based on the abundance of spermatozoa in the testis. The testicular organs were collected and observed using standard histology and transmission electron microscopy (TEM). Ultrastructural observation associated with morphometric analysis showed that spermatozoa are structurally long cells of approximately 51.17 ± 4.54 µm total length, composed of a head, a midpiece and a tail. The head had no acrosome, and the granular structure of condensed chromatin was observed within the ovoid nucleus. The midpiece consisted of a short cylindrical region with the length of 1.29 ± 0.87 µm in diameter, having the centriolar complex organization and eight mitochondria (approx. 0.32 ± 0.02 µm each). The uniflagellar tail was clearly identified with a classical 9+2 arrangements of microtubules. Based on these characteristics, the spermatozoon of wild scalloped perchlet are considered as uniflagellate anacrosomal aquqsperm. The morphological features, including the number of mitochondria, may be used for further cryopreservation and in the evolutionary biology of this species.